Associations Between Nutritional Status, Sociodemographic Characteristics, and Health-Related Variables and Health-Related Quality of Life Among Chinese Elderly Patients: A Multicenter Prospective Study - Liu, Hongpeng; Jiao, Jing; Zhu, Chen; Zhu, Minglei; Wen, Xianxiu; Jin, Jingfen; Wang, Hui; Lv, Dongmei; Zhao, Shengxiu; Wu, Xinjuan; Xu, Tao (Frontiers in Nutrition, 2020)
Background: Studies of the explore nutritional status, sociodemographic factors, mental health variables, physical health variables that affect health-related quality of life (HRQoL) of the elder patients are scarce in China. Objective: This study aims to examine the association between HRQoL and nutritional status, sociodemographic characteristics and health-related variables among Chinese elder patients. Material and methods: Participants were recruited from six tertiary-level hospitals in six provinces or municipality/city throughout China from October 2018 to February 2019, which enrolled 9,996 participants aged 65 years and older. Nutritional status and HRQoL were measured using the Short Form Mini Nutritional Assessment (MNA-SF) and the EuroQoL Five-Dimensions Visual Analog Scale, respectively. BMI was taken using standard measurement protocols. Sociodemographic characteristics included age, sex, education, marital status, ethnicity, smoking, alcohol drinking, current residence. Mental and physical health variables such as frailty and depression were assessed using validated tested instruments. Multiple linear regression analysis was used to analyze whether nutritional status, sociodemographic characteristics, and health-related variables were associated with HRQoL. Results: According to MNA-SF scores at 30- and 90-day follow-up, 9.7% and 9.1% of participants were malnourished, respectively. Higher MNA-SF scores were related to higher HRQoL scores in older patients (regression coefficient; 95% confidence interval) both at 30- (0.660; 0.499, 0.821) and 90-day (0.622; 0.434, 0.809) follow-up. However, there were no significant associations between body mass index values and HRQoL. Sociodemographic characteristics (such as age, smoking, current residence), physical health variables (frailty, urinary function, defecation function, sleeping condition, falling accidents in the past 12 months), and mental health variables (depression) were the main factors influencing HRQoL in this group. Conclusion: There are several factors associated with HRQoL among the population derived from this investigation of a representative sample of the Chinese elderly hospitalized population in tertiary hospitals. These findings could have major importance for the planning of “active aging” policies and programmes.